2014
DOI: 10.1080/1059924x.2014.916643
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment Related to Dermal Exposure of Chlorpyrifos: A Case Study of Rice Growing Farmers in Nakhon Nayok Province, Central Thailand

Abstract: To date, pesticides, especially organophosphate pesticide such as chlorpyrifos, have been frequently applied to paddy fields over time to maintain product quality, protect agricultural crops from various pests, and increase yield. This study evaluates dermal exposure to chlorpyrifos in rice farmers along with providing a health risk assessment. Thirty-five rice farmers participated and completed an in-person interview, and patch technique was used to evaluate dermal exposure to chlorpyrifos. The chlorpyrifos r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…As shown in a study of farmers in Uganda, the main problem was that they did not use proper PPE, which resulted in toxic poisoning from pesticides [13]. This finding is also in line with the study about health risk assessment of farmers in Nakhon Nayok province, Thailand, which found farmers were at risk of adverse health effects due to dermal exposure to chlorpyrifos from the improper use of PPE [14]. In addition, some farmers still performed risky practices of getting pesticides into the body, that is, drinking and eating in the area where spraying was carried out.…”
Section: Relationship Between the Practice Of Pesticide Use And Sche supporting
confidence: 77%
“…As shown in a study of farmers in Uganda, the main problem was that they did not use proper PPE, which resulted in toxic poisoning from pesticides [13]. This finding is also in line with the study about health risk assessment of farmers in Nakhon Nayok province, Thailand, which found farmers were at risk of adverse health effects due to dermal exposure to chlorpyrifos from the improper use of PPE [14]. In addition, some farmers still performed risky practices of getting pesticides into the body, that is, drinking and eating in the area where spraying was carried out.…”
Section: Relationship Between the Practice Of Pesticide Use And Sche supporting
confidence: 77%
“…A cross-sectional survey of 182 rice farmers and 122 controls in Thailand found that rice farmers had significantly higher prevalence of difficulty in breathing and chest pain compared to controls (OR = 2.8; p < 0.01, and OR = 2.5; p < 0.05, respectively). A health risk assessment related to dermal exposure of chlorpyrifos was conducted among 35 rice farmers in Nakhon Nayok Province, Thailand [ 25 ]. About 14% of rice farmers reported blurred vision and dizziness during pesticide application.…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrated that the levels of chlorpyrifos in males (526.34 AE 478.84 mg/kg) were significantly higher than the levels in females (500.75 AE 595.15 mg/kg), and the urinary DAP levels were correlated with dermal exposure. 44,45 Children living in agricultural communities also have a greater potential for exposure to pesticides from the environment and prenatal exposure. In Songkhla Province of southern Thailand, the mean level of urinary DAP metabolites in children who lived in or near vegetable farming areas ranged from 2.14 AE 2.5 lg/g creatinine dimethyl phosphate (DMP) to 8.09 AE 10.2 lg/g creatinine dimethyl thiophosphate (DMTP) for the dry season and 0.71 AE 2.0 lg/g creatinine DMP to 3.26 AE 2.2 lg/g creatinine diethyl phosphate (DEP) for the wet season.…”
Section: Determination Of Pesticide Exposure Levelsmentioning
confidence: 99%
“…The results demonstrated that the levels of chlorpyrifos in males (526.34 ± 478.84 mg/kg) were significantly higher than the levels in females (500.75 ± 595.15 mg/kg), and the urinary DAP levels were correlated with dermal exposure. 44,45…”
Section: Determination Of Pesticide Exposure Levelsmentioning
confidence: 99%